Lewy body dementia - Taylor, John-Paul (Henry Stewart Talks, 2021)
Lewy body dementia (LBD), Underdiagnosis of Dementia with Lewy Body (DLB), DLB Outcomes, Prevalence of DLB in the UK, Clinical diagnostic criteria, Problems in diagnosing dementia with Lewy bodies, The DIAMOND Lewy study, The Diagnostic assessment toolkit, Management of dementia with Lewy bodies, Targeting alpha-synuclein